Limiares de urbanização atuam como filtro ambientalnas comunidades de peixes na Bacia do Rio Sorocaba: uma análise sob a lente da diversidade funcional em relação ao uso e ocupação do solo - Baldini, Gustavo Alves (Universidade Federal de São Carlos, 2026)
The Atlantic Forest is an important biodiversity hotspot and is embedded within an increasingly anthropized matrix. Recognizing the effects of anthropogenic pressure on species diversity patterns may be a way to identify potential threats and contribute to the direction of conservation actions. Species diversity within a community can be quantified through different approaches, including functional diversity, which corresponds to the roles performed by species within the ecosystem. In this study, we analyzed the variation in the functional diversity of stream fish as a function of anthropogenic pressure exerted on fish communities inhabiting streams distributed along an anthropization gradient in the Sorocaba River basin, in the state of São Paulo, Brazil. To achieve this, functional diversity indices were calculated based on morphometric and trophic measurements of stream fish collected over a six-year period. Anthropogenic pressure was quantified using an Anthropogenic Pressure Index (API), calculated according to land use and land cover in the study area at two spatial scales: buffer and sub-basin. The data obtained were then subjected to linear regression analysis to test the correlation between functional diversity and anthropization. The structure of fish assemblages was analyzed in 45 stream reaches, totaling 40 species from 14 families. A high taxonomic dominance of a few generalist species was observed, especially Phalloceros reisi (FO = 0.82) and Poecilia reticulata, which together with the family Characidae accounted for more than 70% of total abundance. Local richness ranged from 1 to 13 species (S̅ = 5.91), with an average Shannon diversity of 1.09 nats/ind., reflecting simplified and numerically dominated communities. Ecomorphological characterization indicated that locomotion is the main axis of functional differentiation, whereas feeding traits showed lower variation. The trophic structure revealed the importance of autochthonous resources, with 60% of the species classified as benthic invertivores and 37.5% as omnivores. The functional space, constructed from four axes (78.26% of explained variance), demonstrated that functional richness (FRic) is maintained through the complementarity of multiple lineages (Characiformes, Siluriformes, Synbranchiformes, Gymnotiformes, and Cyprinodontiformes), highlighting that functionally unique taxa are fundamental to niche volume regardless of their abundance. Analysis of anthropogenic pressure (API) revealed that urbanization reaches critical levels (>84%) in degraded stream reaches. The relationship between API and functional diversity (FDis) proved to be scale-dependent: at the buffer scale, the relationship was non-significant, whereas at the sub-basin scale, a significant quadratic pattern (“inverted U-shape”, R² = 16.1%) was observed. This result indicates that functional diversity responds to urbanization thresholds, undergoing severe contractions only after surpassing a critical level of stress within the watershed. It is concluded that land use and land cover at the sub-basin scale act as the predominant environmental filter, and that maintaining functional integrity depends on management strategies that consider land use at this scale.
Urbanization thresholds act as an environmental filter for fish communities in the Sorocaba River Basin: an analysis through the lens of functional diversity in relation to land use and land cover
Keywords: Comunidade biológica; Mata Atlântica; Antropização; Biological community; Atlantic Forest; Anthropization; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA; 3. Saúde e Bem-Estar